Normative values for interlimb symmetry in single-leg vertical jump height among uninjured adolescent athletes - VanZile, A. W.; Jones, D. D.; Almonroeder, T. G. (International Journal of Athletic Therapy & Training, 2025)
The lack of normative data for single-leg vertical jump testing makes it challenging to determine when an injured athlete has achieved a level of interlimb symmetry that is within normal limits. The purpose of this study was to establish normative values for single-leg vertical jump height interlimb symmetry based on data from uninjured adolescent athletes. One hundred seventy three uninjured adolescent athletes completed single-leg vertical jump testing with both limbs. Descriptive statistics were generated to summarize the percent differences in jump heights between the limbs (interlimb symmetry) for the male and female athletes. Having normative data available will help clinicians assess injured athletes` recovery.